Communicating the Risk of MRSA: The Role of Clinical Practice, Regulation and Other Policies in Five European Countries - Dickmann, Petra; Keeping, Sam; Döring, Nora; Schmidt, Andrea E.; Binder, Claudia; Ariño-Blasco, Sergio; Gil, Joan (Frontiers in Public Health, 2017)
Background: The threat posed by Meticillin-resistant Staphylococcus aureus (MRSA) has taken on an increasingly pan European dimension. This article aims to provide an overview of the different approaches to the control of MRSA adopted in five European countries (Austria, Germany, Netherlands, Spain and the UK) and discusses data and reporting mechanisms, regulations, guidelines and health policy approaches with a focus on risk communication. Our hypothesis is that current infection control practices in different European countries are implicit messages that contribute to the health-related risk communication and subsequently to the public perception of risk posed by MRSA. A reporting template was used to systematically collect information from each country. Discussion: Large variation in approaches was observed between countries. However, there were a number of consistent themes relevant to the communication of key information regarding MRSA including misleading messages, inconsistencies in content and application of published guidelines, and frictions between the official communication and their adoption on provider level. Summary: The variability of recommendations within, and across, countries could be contributing to the perception of inconsistency. Having inconsistent guidelines and practices in place may also be affecting the level at which recommended behaviours are adopted. The discrepancy between the official, explicit health messages around MRSA and the implicit messages stemming from the performance of infection control measures should therefore be a key target for those wishing to improve risk communication.